2013
DOI: 10.1002/ceat.201200725
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Automated Ad‐ and Desorption Method for Resin and Solvent Screening

Abstract: Ad‐ and desorption are common techniques for the purification of natural substances. The main drawback is the tedious experimental procedure for resin and solvent screening. An approach of fully automated batch experiments is presented. In order to fulfill all requirements like automation of flexible dosing of loose resins, handling organic solvents, and providing reproducible conditions, these experiments are performed on a custom‐built modular robotic platform. The batch ad‐ and desorption experiments were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…The automated platform Lipos GXXL (Zinsser Analytic) offers the opportunity to handle and weigh liquid as well as nonpacked solid materials, e.g., powders in a highly accurate way. This has been proved by Schuldt et al in a case‐study for ad‐ and desorption experiments 10. The solid handling is a unique feature which expands the potential of automated experimental investigation for a variety of unit operations and increases the functionality while reducing the experimental effort and supporting manual investigation at the same time.…”
Section: Introductionmentioning
confidence: 90%
“…The automated platform Lipos GXXL (Zinsser Analytic) offers the opportunity to handle and weigh liquid as well as nonpacked solid materials, e.g., powders in a highly accurate way. This has been proved by Schuldt et al in a case‐study for ad‐ and desorption experiments 10. The solid handling is a unique feature which expands the potential of automated experimental investigation for a variety of unit operations and increases the functionality while reducing the experimental effort and supporting manual investigation at the same time.…”
Section: Introductionmentioning
confidence: 90%
“…The PTFE tip has an aspiration limit of 65 mg per dosage step, and multiple dosage Figure 1. Top view of the robot platform: (1) washing station, (2) notched metal platform, (3,4) disposable Teflon tip reservoir, (5) four racks for 8-mL vials, (6) two racks for 1.5-mL vials, (7) crimp station, (8) closing cap reservoir, (9,26) filter reservoir, (10) filtration station, (11,12) lid for vortex station, (13) purging station of the powder pipette, (14) teeterboard, (15) vessel for solids, (16) balance, (17) powder needle, (18) one rack for vortex station, (19) two racks for centrifugation, (20) source rack for 50-mL vials, (21) centrifuge, (22,23) push buttons, (24,25) grippers, (27) vortex station connected to a thermostat, (28,29) pH electrode, purging and titration station. steps are needed for higher amounts.…”
Section: Accuracy and Precision In Solid Handlingmentioning
confidence: 99%
“…In addition, an automated solid-to-solid weighing workstation with electrostatically charged pipette tips was described and implemented [19]. Currently, more complex operations such as batch adsorption and desorption are used to determine essential process parameters for kinetics and equilibrium isotherms [20].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, systematic process development based on identification of justified optima is essential for efficient utilization of time and resources. Nfor et al (2009) identified four types of process synthesis strategies applicable to chemical industries: heuristics or knowledge-based strategies (Cziner et al, 2005), optimization-based strategies (Steimel et al, 2013;Grossmann and Daichendt, 1996), high-throughput experimentation strategies (Bhambure et al, 2011;Schuldt and Schembecker, 2013) and a combination of the aforementioned strategies (Ahamed et al, 2006). Each approach has strengths and weaknesses as discussed elsewhere (Nfor et al, 2009).…”
Section: Introductionmentioning
confidence: 98%